Factors Affecting Academics Professional Development of Higher Education Institutions - Elatawneh, Hebah Ahmed Ali; Sidek, Safiah; Abo Mosali, Najmaddin (International Journal of Sustainable Construction Engineering and Technology, 2022)
Several challenging contributions linked to the standard of teaching in higher education institutions and one of them is academic professional development programs. The challenge is so obvious due to structural changes in a modern society that requires an improvement to the teaching quality. Hence, this paper presents a study on determine the factors affecting academics professional development in UAE higher learning institution. There are 63 factors that were clustered into seven groups of factors namely design teaching plan; communication skills; expertise skill in the lesson content; individual and occupational; policy and strategy; technological factors; and teaching skills. The collected data from the questionnaire survey was analysed to determine the ranking of the seven groups’ factors it was found that communication skills group of factors is the most influencing factor affecting academics professional development. The following factor is the design of teaching plan factors ranked as second and policy and strategy factors ranked as third place. The collected data was also analysed using cross tabulation approach and found that for professor concerned is communication skills and the least concerned is individual and occupational identity. While for associate professor, the concerned factor is the expertise skill in the lesson content and the least concerned is communication skills. For senior lecture, the most concerned is design of teaching plan and the least concerned is technology. Finally for lecturer, the most concerned is design of teaching plan and the least concerned is individual and occupational identity. The findings from this study will benefit related parties in formulating their professional development programs for the academics.